ISLAMIC COSMOGONY ACCORDING TO SÅªRAH AL-á¸¤ASHR VERSE 24: â€œHE IS ALLÄ€H, THE CREATOR, THE ORIGINATOR, THE FASHIONER OF FORMSâ€ - Longhurst, Christopher Evan (European Scientific Journal, ESJ, 2014)
SÅ«rah al-á¸¤ashr verse 24 states: â€œHe is AllÄh, the Creator, the Originator, the Fashioner of Forms.â€ The corresponding canonical terms in Arabic are Al-KhÄliq, Al-BÄrÄ«â€™, and Al- Muá¹£awwir although their meanings are quite richer than the English transliterations suggest. By taking up those meanings this paper offers insights into Islamâ€™s theory of the universeâ€™s origin and development with implications for both Islamic theology and its philosophy of science. It enquires into the meaning of this Äyah in light of tafsir (exegesis) on the three divine names in order to establish a theological basis for Islamic cosmogony. It presents Al- KhÄliq as the creative power of the divine intellect, Al-BÄrÄ«â€™ as the creative agency of the divine will, and Al-Muá¹£awwir as the creative action of the divine wisdom. This contextualization is further developed by identifying Al-KhÄliq with the causa prima of creation, the supposed creatio ex nihilo (out of nothing), and both Al-BÄrÄ«â€™ and Al-Muá¹£awwir as the causa secunda of a creatio ex materia sed semper noviter (out of matter though always anew). Conclusions reached will assert that SÅ«rah al-á¸¤ashr verse 24 is Islamâ€™s own â€œtheological statementâ€ regarding the worldâ€™s origin and continued creation. It presents creation as both an event and a process, and unfolding in time, the basis and quintessence of Islamâ€™s unique cosmogony.